Model to Stimulate Economic Growth in Indonesia - Abdullah, Ridwan; Ahmad, Masduki; Rochimah, Heni (Universitas Pahlawan Tuanku Tambusai, 2025)
Educational investment as part of human capital development is a crucial strategy in increasing competitiveness and driving economic growth of a nation. However, in developing countries like Indonesia, there is still a gap between theory and practice, particularly in the effectiveness of implementing education financing models. This study aims to formulate a relevant human capital- based education financing model capable of driving inclusive and sustainable economic growth. Using a systematic literature study approach to scientific publications and national-international policy documents over the past decade (2014–2024), it was found that education financing schemes focused on improving the quality of human resources have a positive impact on labor productivity and Gross Domestic Product (GDP) growth. The findings demonstrate the importance of implementing outcome-based budgeting, diversifying funding sources, and cross-sector synergy in formulating education financing policies. The proposed conceptual model positions human resource quality as the main indicator of the effectiveness of education investment. In conclusion, education financing strategies must be designed contextually, collaboratively, and output-oriented to encourage inclusive and sustainable economic growth.